PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA KELAS V SEKOLAH DASAR 96 PALEMBANG - Hidayah, Anugra; Hodsay, Zahrudin; Pratama, Aldora (Faculty of Teacher Training and Education, 2025)
This research was conducted with the aim of finding out the effect of giving rewards regarding the learning motivation of class V students at SD 96 Palembang. The research method used is True Experimental, this research method is quantitative. The research subjects were fifth grade students at SD 96 Palembang. Based on the results of research data analysis, it was found that the experimental class posttest data results for the experimental class obtained an average score of (1,627) while the posttest data results for the control class were (1,475), it can be concluded that the average total score for the experimental class was greater than the control class. Based on the results of data research that was carried out at SD 96 Palembang, this statement can be proven by the results of the independent sample T-test, namely that a significant value (2-tailed) was obtained of 0.004 with a significance level of 0.05 because the significant value was 0.004>0.05 and tcount (3,180) ttable (1,706) then based on the hypothesis examination criteria HO is rejected and Ha is accepted. So it can be concluded that there is an influence of giving rewards on the learning motivation of class V students at SD 96 Palembang.Keywords: Giving Reward, Student Learning Motivations